Design a rehabilitation program to treat some soft tissue injuries in the shoulder joint of basketball people - Salman, Sahar Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Objective: The study aimed to identify the differences between the measurements (tribal dimension) for the rehabilitation and treatment of some soft tissue injuries in the shoulder joint in the tests under study, participants: basketball players in the specialized school (Iraq) numbered (8) players injured in the shoulder joint, The researcher used the experimental method using the experimental design of one group and measurement (tribal-dimensional) to suit the nature and purpose of the research, the researcher has conducted a number of tests and selected measurements that are suitable for the age and sex of the research sample members being young and that are consistent with The requirements of the research, and a rehabilitation program was designed according to physical exercises for the rehabilitation of shoulder joint injuries, which are exercises without weight, exercises using body weight, medical balls and exercises using iron bar, and used the law (T TEST) for non-independent samples to know the difference between tribal and dimensional testing, it was reached that the rehabilitation method has a positive effect in the treatment of some soft tissue injuries (muscles, wallet ligaments) in the shoulder joint in light of the results in the tests (tribal and dimension).